Immunodiagnosis — the promise of personalized immunotherapy - Wang, Renjie; Xiong, Kairong; Wang, Zhimin; Wu, Di; Hu, Bai; Ruan, Jinghan; Sun, Chaoyang; Ma, Ding; Li, Li; Liao, Shujie (Frontiers in Immunology, 2023)
Immunotherapy showed remarkable efficacy in several cancer types. However, the majority of patients do not benefit from immunotherapy. Evaluating tumor heterogeneity and immune status before treatment is key to identifying patients that are more likely to respond to immunotherapy. Demographic characteristics (such as sex, age, and race), immune status, and specific biomarkers all contribute to response to immunotherapy. A comprehensive immunodiagnostic model integrating all these three dimensions by artificial intelligence would provide valuable information for predicting treatment response. Here, we coined the term “immunodiagnosis” to describe the blueprint of the immunodiagnostic model. We illustrated the features that should be included in immunodiagnostic model and the strategy of constructing the immunodiagnostic model. Lastly, we discussed the incorporation of this immunodiagnosis model in clinical practice in hopes of improving the prognosis of tumor immunotherapy.